How dose Meeting, Incentive, Conventions, Exhibitions (MICE) Industry survive through Covid-19 era? - Somsawat, Sorrawat; Tananpang, Chonmani (Journal of Innovation and Management, 2020)
The purpose of this article is to analyze the organizational adaptation in MICE industry from the spread of Covid-19. The emergence of a novel coronavirus (COVID-19) has been threatening the livings of worldwide people in the aspects of health, property, and economy which could affect almost all sectors of business. One of these businesses is the MICE industry which is considered as the most significant economic machine of Thailand capable of creating an industrial value of above a hundred thousand million baht per year. In the preceding period of the COVID-19 outbreak, the MICE industry has yielded the lowest revenue in the last 10 years. The businesses could not be conducted due to the contradiction to the social distancing measure, causing the income rapidly decreased more than 60 percent. For the business retention purpose, the entrepreneurs have commenced the adjustment by organizing the activity to be consistent with the new normal emerged, by applying virtual meeting for the broadcasting of online meeting including seeking the new business model. However, these changes have limitations. They are only suitable for certain businesses in the MICE industry. Therefore, the way to make the whole system survive is merging the adaptation between internal and external factors - that is to say, applying technology with the management, the leadership, the policy, the measure, and the rule. To grow sustainably, the short-term operations must be considered first which is harmoniously adaptation to the current situation. The following step is the long-term operations which are the personnel, the promoting a learning organization, the effective management. Lastly, the organizational leadership which will create high performance enhances the vitality of MICE industry in Thailand.